A Fortuitously Straightforward Synthesis of 4-Acetoxy-2-Propyltetrahydrothiophene. (December 2015) - Ma, Bianbian; Yang, Shaoxiang; Tao, Feiyan; Sun, Baoguo; Liu, Yongguo; Tian, Hongyu
4-Acetoxy-2-propyltetrahydrothiophene was synthesised from 1-hepten-4-ol by a three-step route involving epoxidation and mesylation to 1, 2-epoxy-4-heptyl mesylate and then reaction with thioacetate. An acetoxylated cyclic product was formed instead of the expected thioacetate, and a mechanism for its formation using an intramolecular transesterification is proposed.